PENYEDIAAN TEMPAT SAMPAH DAN SAPU LIDI UNTUK MENUNJANG KEBERSIHAN LINGKUNGAN MASYARAKAT DI DESA HILILAZA KECAMATAN TELUK DALAM KABUPATEN NIAS SELATAN - Pengalaman Dakhi; Lilismawati Duha; Nemia Srida Y. Manao; Antonius Buulolo; Enjelita Zalogo; Niar Silis D. Maduwu; Nilda Claresta Saota; Efodian Maruao; Yakin Kasih Ndruru; Erniwati Zebua; Ika Sri F. Finowa’a; Anita Zagoto (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service program conducted by Nias Raya University is called KKN (real work lecture). The objectives of this KKN activity include implementing community service, introducing students to community life, expanding good relations between the university and the government and target communities, and helping to establish the availability of village data or profiles by identifying and analyzing data that can be used for village development planning with the target of sustainable development goals. The KKN progam was implemented in several villages in south Nias Regency, one of which was Hililaza Village, teluk dalam District, South Nias Regency, from july 12 to august 22, 2025. Hililaza village is located in Teluk Dalam sub district, South Nias Regency. Hililaza village apprears to be quite good in several aspects, including social and economic aspects, as well as the android system. The community service program (KKN) begins with a village observation process to explore the village and see the potential of the village which will be the main target in the implementation of KKN. The programs are designed sequentially starting with discussions between KKN groups, village officials, and the local community,especially those directly involved in the designed programs. The implementation of the KKN program is carried out in a balanced manner, starting with planning, implementation, and evaluation at the end of each program. The results achieved from the entire KKN program include making trash bins, broomsticks , making sapta pesona, carrying out mutual cooperation, and celebrating the anniversary of the Indonesian Ministry of Education and Culture on August 17, 2025.